Synthesis of a metal-chelating polymer with NOTA pendants as a carrier for 64Cu, intended for radioimmunotherapy. (15th February 2020) - Cho, Hyungjun; Liu, Peng; Boyle, Amanda J.; Reilly, Raymond M.; Winnik, Mitchell A.
Graphical abstract: Highlights: Metal-chelating polymers (MCPs) with NOTA and either mPEG12 or methoxyethyl pendant groups were synthesized. The metal-chelating polymers were radiolabeled with 64 Cu and injected into healthy Balb/c mice. Potential reasons for the unusually high kidney uptake the MCPs were discussed. Abstract: As a positron emitter, 64 Cu is useful for positron emission tomography. It can also generate Auger electrons that are useful for therapy. Many radioimmunoconjugates labelled with 64 Cu involve covalent attachment of bifunctional chelators directly to the antibody (Ab) of interest. To increase its therapeutic potential, a metal-chelating polymer (MCP) with multiple chelators can be conjugated the Ab. In this way, one can incorporate multiple 64 Cu ions per Ab. Here we describe the synthesis of a MCP designed for attachment to trastuzumab (tmab), an antibody (Ab) used to treat breast cancer patients with tumours that overexpress human epidermal growth factor receptor 2. We chose 1, 4, 7-triazacyclononane-N, N', N''-triacetic acid (NOTA) chelator to complex with 64 Cu, and in our design, the polymer would carry multiple copies of the NOTA chelator as pendant groups. The Cu 2+ /NOTA complex has a net negative charge. We began by using RAFT polymerization to synthesize an end-functional poly(2-aminoethyl acrylamide) polymer, in which we could use the amino groups to attach the chelator and other substituents. In a previous study (Biomacromolecules. 13 (2012) 2831–2842), we found that MCP radioimmunoconjugates with a negative charge in the repeat unit led to high liver up-take in a mouse model. Thus, we chose to introduce ca. 50% methoxy-dodecaethylene glycol (mPEG12 ) pendant groups to confer "stealth". As a control, we also synthesized a similar polymer with ca. 50% methoxyethyl pendants (EO1 ). NOTA chelators were attached to remaining pendant groups. We then end-capped the MCPs with succinic acid, radiolabeled the MCPs with 64 Cu and injected the radiolabeled MCPs into healthy Balb/c mice via the tail vein. We observed that a large amount of the MCPs were retained in the kidneys. We discuss what properties of the MCPs may have contributed to its accumulation in the kidneys.